Attainment of Program Outcome ’3B’ of ABET through Laboratory Experiment for the Undergraduate Program - Jangali Satish, G.; Lakkundi, Anand R.; Gaitonde, V. N.; Burli, S. B.; Madhusudhana, H. K. (Journal of Engineering Education Transformations, 2015)
The engineering education has gone through several re-engineering efforts under various names. Some of the popular names in the past have been sustainable engineering and concurrent engineering. While each of these names has a different flavor to it, the underlying principle of effective engineering education has been its ability to provide practical and functional learning opportunities to students. Experiential learning, which encompasses all types of practice-based learning opportunities, is the founding principle of a successful engineering education model. This paper presents an approach to enhance active and collaborative learning in ’Metal Cutting’ laboratory by the undergraduate students of V Semester Industrial&Production Engineering using the concept of "Design of Experiments", to study the effects of various parameters on machining performance. The paper also describes the assessment of program outcome ’3b’ of ABET criteria through laboratory experiment.